The Magpies, the Prize and Coleridge’s Imagination: the Creation Records Story - Campbell, Colin (Scenari, 2021)
This article examines David Cavanagh’s history of Creation Records, My Magpie Eyes are Hungry for the Prize, as an exemplary microcosm of the evolution of British rock music and popular culture more generally in the neoliberal era, which now features resurgent forms of populist nationalism. The essay marks a magpie’s flight, taking an irregular path through a history of the picaresque, alighting on Ovid, English folk-rhyme, and finally settling noisily in the territory of post-punk and indie rock. The overall premise is that, in the unlikely venue of pop music journalism, Cavanagh’s achievement was to articulate the link between post-punk/indie-rock and the Imagination in Samuel Taylor Coleridge’s sense.